2013
DOI: 10.1080/13607863.2013.823375
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of cognitive dysfunction in chronic hemodialysis patients

Abstract: There is a high prevalence of cognitive dysfunction among hemodialysis patients and many causative factors have been evoked. Effective identification of this trouble allows adequate psychological interventions to improve the quality of life of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 17 publications
3
20
0
3
Order By: Relevance
“…This and similar studies cited have unanimously concluded that cognitive impairment is worryingly common in patients with renal failure. The prevalence of cognitive impairment was reported as 18.8% in Japanese patients undergoing hemodialysis (12) and as 25% in Moroccan patients by Wechsler memory test (16). Different studies have thus reported different prevalence rates for cognitive impairment in hemodialysis patients; this disparity may be attributed to the different diagnostic methods used, the different measures used for assessing cognitive impairment and the different sample populations examined and methods of sampling used.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…This and similar studies cited have unanimously concluded that cognitive impairment is worryingly common in patients with renal failure. The prevalence of cognitive impairment was reported as 18.8% in Japanese patients undergoing hemodialysis (12) and as 25% in Moroccan patients by Wechsler memory test (16). Different studies have thus reported different prevalence rates for cognitive impairment in hemodialysis patients; this disparity may be attributed to the different diagnostic methods used, the different measures used for assessing cognitive impairment and the different sample populations examined and methods of sampling used.…”
Section: Discussionmentioning
confidence: 96%
“…For example, Odagiri et al (12) argued that hemodialysis treatment is an independent risk factor for cognitive impairment in patients with renal failure. Fadili et al (16) also found that lower levels of education and anemia are risk factors for the incidence of cognitive impairment in patients undergoing hemodialysis. In a study by Eslami-Amirabadi et al (15), cognitive impairment was found to be associated with age, lower levels of education and diabetes mellitus, depression and positive qualitative CRP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations